Identification of Critical Incidents in Practicing Teachers: Proposals for Lifelong Learning - Gilda Bilbao Villegas; Carles Monereo Font (Universidad Autónoma de Baja California, 2011)
Given the challenges of teaching today-an activity marked by information overload, technological changes and heterogeneity in the classroom-we find teachers who experience day by day, in the management of their classes, a number of critical incidents (CI) which cause them uncertainty and emotional destabilization. In the present study we have attempted to make a deep and careful study of the types of CI and the impact they have, as well as the strategies used by teachers to address them. At first the information was obtained through a focus group; the data obtained were compared with the results of the questionnaire administered to a sample. The study notes that the reported CI are primarily related to class management and students' attitude toward learning. Also highlighted is the teachers' lack of psychopedagogical and emotional resources for dealing with the CI.